Psychosocial Attention Center Alcohol and Other Regional Drugs: Potentiality and Obstacles (Research, Society and Development, 2022)
The device that orders care in the territory recommended by the Psychiatric Reform Law is the Psychosocial Care Centers. In the four decades since the beginning of the anti-asylum movement, many advances have taken place, but today it is possible to perceive the lack of credibility with the Mental Health Policy in the spheres of government, going back in the forms of treatment. This scenario enhances this study, which aims to evaluate a regional Psychosocial Care Center for alcohol and other drugs based on the potential and obstacles identified by different interest groups. Of a qualitative nature, the Fourth Generation Assessment was used. The collection period was between May and November 2018 through documentary research, semi-structured interviews and focus groups. Interest groups were selected to define the participants: managers, workers and users. The thematic groups were: the regional configuration, intersectoriality and matrix support. The conclusion was that regionalization, used as a management strategy, needs regular renegotiations between managers to ensure the functioning and assistance to the treatment; intersectoriality and matrix support, facilitators of expanded care, have the greatest obstacles in the distance and in the definition of roles of network services.